Comparative Chloroplast Genome Analyses of Streptophyte Green Algae Uncover Major Structural Alterations in the Klebsormidiophyceae, Coleochaetophyceae and Zygnematophyceae - Lemieux, Claude; Otis, Christian; Turmel, Monique (Frontiers in Plant Science, 2016)
The Streptophyta comprises all land plants and six main lineages of freshwater green algae: Mesostigmatophyceae, Chlorokybophyceae, Klebsormidiophyceae, Charophyceae, Coleochaetophyceae and Zygnematophyceae. Previous comparisons of the chloroplast genome from nine streptophyte algae (including four zygnematophyceans) revealed that, although land plant chloroplast DNAs (cpDNAs) inherited most of their highly conserved structural features from green algal ancestors, considerable cpDNA changes took place during the evolution of the Zygnematophyceae, the sister group of land plants. To gain deeper insights into the evolutionary dynamics of the chloroplast genome in streptophyte algae, we sequenced the cpDNAs of nine additional taxa: two klebsormidiophyceans (Entransia fimbriata and Klebsormidium sp. SAG 51.86), one coleocheatophycean (Coleochaete scutata) and six zygnematophyceans (Cylindrocystis brebissonii, Netrium digitus, Roya obtusa, Spirogyra maxima, Cosmarium botrytis and Closterium baillyanum). Our comparative analyses of these genomes with their streptophyte algal counterparts indicate that the large inverted repeat (IR) encoding the rDNA operon experienced loss or expansion/contraction in all three sampled classes and that genes were extensively shuffled in both the Klebsormidiophyceae and Zygnematophyceae. The klebsormidiophycean genomes boast greatly expanded IRs, with the Entransia 60,590-bp IR being the largest known among green algae. The 206,025-bp Entransia cpDNA, which is one of the largest genome among streptopytes, encodes 118 standard genes, i.e. four additional genes compared to its Klebsormidium flaccidum homolog. We inferred that seven of the 21 group II introns usually found in land plants were already present in the common ancestor of the Klebsormidiophyceae and its sister lineages. At 107,236 bp and with 117 standard genes, the Coleochaete IR-less genome is both the smallest and most compact among the streptophyte algal cpDNAs analyzed thus far; it lacks eight genes relative to its Chaetosphaeridium globosum homolog, four of which represent unique events in the evolutionary scenario of gene losses we reconstructed for streptophyte algae. The ten compared zygnematophycean cpDNAs display tremendous variations at all levels, except gene content. During zygnematophycean evolution, the IR disappeared a minimum of five times, the rDNA operon was broken at four distinct sites, group II introns were lost on at least 43 occasions, and putative foreign genes, mainly of phage/viral origin, were gained.